Предмет:
ХимияАвтор:
marisoltownsendОтвет:
ch3-ch2-ch=ch-ch(-ch3)-ch2-ch3 5-метилгептен-3
ch3-ch=ch-ch2-ch(-ch3)-ch2-ch3 5-метилгептен-2
ch2=ch-ch2-ch-ch(-ch3)-ch2-ch3 5-метилгептен-1
ch3-ch2-ch2-ch=c(-ch3)-ch2-ch3 5-метилгептен-4
ch3-ch2-ch2-ch2-c(-ch3)=ch2-ch3 5-метилгептен-5
ch3-ch2-ch2-ch2-ch(-ch3)-ch2=ch3 5-метилгептен-6
ch3-ch2-ch=c(-ch3)-ch2-ch2-ch3 4-метилгептен-3
ch3-ch2-ch=ch-ch2-ch(-ch3)-ch3 6-метилгептен-3
ch2(-ch3)-ch2-ch=ch-ch2-ch2-ch3 1-метилгептен-3
ch3-ch2-c(-ch3)=ch-ch-ch2-ch3 3-метилгептен-3
ch3-ch(-ch3)-ch=ch-ch2-ch2-ch3 2-метилгептен-3
Автор:
tyson40Добавить свой ответ
Предмет:
МатематикаАвтор:
abelardoj5ygОтветов:
Смотреть
Предмет:
МатематикаАвтор:
londynОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
baileyplf6Ответов:
Смотреть